Dynamic cause of saltwater intrusion extremes and freshwater challenges in the Changjiang Estuary in flood season of 2022 - Rui Ma; Cheng Qiu; Jianrong Zhu; Zhilin Zhang; Yiping Zhu; Lingting Kong; Lei Ding; Wei Qiu; Hui Wu (Frontiers in Marine Science)
Estuarine regions heavily rely on the supply of freshwater from rivers, which could suffer saltwater intrusion. In the late summer and autumn of 2022, the Changjiang basin experienced prolonged severe drought, resulting in the river discharge decreasing to its lowest level according to historical records. Furthermore, the Changjiang Estuary was affected successively by three typhoons in September. Saltwater intrusion extremes have occurred since early September, resulting in the Qingcaosha Reservoir, the largest estuarine reservoir in the world, being unsuitable for water intake for 98 days. This has seriously threatened the safety of the water supply in Shanghai. No such extremely severe event has occurred since salinity has been recorded in the estuary, even in the dry season. Our findings show that saltwater intrusion extremes were caused by the combined effect of extremely low river discharge and typhoons, which drove substantial landward water transport to form a horizontal estuarine circulation flowing into the North Channel and out of the South Channel. This landward net water transport overcame seaward runoff and brought highly saline water into the estuary. The extremely low river discharge is the fundamental cause for the severe saltwater intrusion, and the typhoons greatly amplified it. The surface and bottom salinities at the water intake of the Qingcaosha Reservoir were amplified 9.6 and 23.4 times by Typhoon Hinnamonr and 10.1 and 15.1 times by Typhoon Nanmadol, respectively. We reveal the dynamic cause of saltwater intrusion extremes, which is conducive for developing effective response measures for estuarine freshwater resources safety.